The Qur'anic View on the Idea of Character Education - Fauzan, Fauzan; Hairit, Artamin; Ansori, Raden Ahmad Muhajir; Dannur, Moh.; Alfiansyah, Alfiansyah (International Conference on Islamic Studies, 2023)
The nation's conduct and culture have evolved as a result of the dialectic of life in this century. Because globalization has both beneficial and harmful effects. Because it can influence human life in terms of behavior, society, and even creed, this detrimental impact must be stopped. Through the development of components, such as cognitive, emotive, and psychomotor, character education must be able to prepare people to deal with the changing times. For Muslims, the Qur'an serves as a universal manual that balances the development of the mind, the heart, and the spirit. Morality is the term used in Islam to describe character education. Morality is split into two categories: morality toward Allah (the Creator) and morality toward other living things. Morality toward Allah is a form of obedience in carrying out all of HIS commands and avoiding His prohibitions, such as monotheism, obeying orders, being sincere in all of one's deeds, praying to Allah and being full of hope (raja'), atoning for one's mistakes, being pleased with all of Allah's decrees, being kind to Allah's provisions, and refraining from despicable traits against Allah like shirk and kufr, among others.Morality toward other people, morality toward other living things, and morality toward the environment and the cosmos are the three categories of morality toward organisms. Morals towards other people, like being patient, apologetic, honest, gentle, inferior, spreading compassion, being obedient to parents, and others. moral principles that prioritize safeguarding and providing for other living creatures, nature, and the environment.